2020
DOI: 10.1101/2020.06.19.161158
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are isokinetic leg torques and kick velocity reliable predictors for competitive success in taekwondo athletes?

Abstract: 27The aim of the study was to analyzed the relationship between isokinetic knee 28 and hip peak torques and Roundhouse-kick velocities and expertise level (Elite vs. 29 Subelite) of Taekwondo athletes. Seven elite and seven sub-elite athletes were tested for 30 kick kinematic, power of impact and for isokinetic peak torque (PT) at slow (60 o /s) and 31 high (240 o /s) concentric mode. PTs were compared between groups and correlated with 32 the data of kick performance. It was found inter-group differences i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…PC1 explained more of the variance in kinematics for the elite subjects than for the sub-elite subjects across all conditions (Table 3). This indicates that the movement of hip and knee is more closely coordinated for the elite subjectsthe hip being a relatively more important driver of the movement, which is in line with previous research suggesting that hip muscle strength is probably the dominant muscular factor for determining kick performance (Moreira et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…PC1 explained more of the variance in kinematics for the elite subjects than for the sub-elite subjects across all conditions (Table 3). This indicates that the movement of hip and knee is more closely coordinated for the elite subjectsthe hip being a relatively more important driver of the movement, which is in line with previous research suggesting that hip muscle strength is probably the dominant muscular factor for determining kick performance (Moreira et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…A high level of kick combination and a good balance is necessary to hit the right spot and win the game in TKD (Kim et al, 2011). Since it is known that the most active muscles during kick strokes are the gastrocnemius, Q and H muscles (Sorensen et al, 1996), knee extensor and flexor strengths are of great importance (Moreira et al, 2020). Kim et al (2015) did not observe any significant difference between Ex and Flx values of the angular velocities of 60°/s and 180°/s, as well as the balances evaluated by the flamingo balance test, in the measurements performed on female TKD practitioners following 1-year regular TKD training.…”
Section: Discussionmentioning
confidence: 99%
“…Seo et al (2015) observed an increase in isokinetic knee strength and anaerobic capacity at an angular velocity of 60°/s with the 8-week training they applied to university-age male and female TKD practitioners. Moreira et al (2020) examined the relationship between the isokinetic strengths of the knee and kinematic data of TKD practitioners, and reported that the angular velocity of 60°/s revealed higher and significant correlations compared to 240°/s in parameters such as preparation time of kick and kick time. This is also a clear indication that the Q and H muscles, which show slow but strong contraction during the pre-kick preparation period and the kick, can also be associated with success in TKD.…”
Section: Discussionmentioning
confidence: 99%